Dispensable role of the human immunodeficiency virus type 2 Vpx protein in viral replication. - Marcon, L (1991)
Human immunodeficiency virus type 2 (HIV-2) is similar in genetic organization to HIV-1 but contains a unique gene (vpx) that encodes a 16-kDa protein. A replication-competent molecular clone of HIV-2 (HIV-2sbl/isy) that infects human primary cells in vitro and rhesus monkeys was used to generate three mutations in the vpx gene. In the first mutant, the vpx open reading frame was truncated at amino acid 20; the second mutant was tailored to eliminate the proline-rich carboxyl terminus of the protein; and the third mutant was obtained by addition of four amino acids (KDEL) to the carboxyl terminus of the protein to provide a retention signal in the endoplasmic reticulum. The viral infection kinetics of the three mutant viruses and isogeneic HIV-2sbl/isy in the SupT1 cell line were similar. Slight impairment in the early phases of viral replication was observed during infection of primary human peripheral blood mononuclear cells with the vpx mutant viruses. All of the vpx mutant viruses readily infected macrophages, indicating that vpx expression is dispensable for HIV-2 infection and replication in human macrophages.